Perancangan Aplikasi Sistem Wedding Organizer Berbasis Web - Faizi, Billy Nur; Sitio, Sartika Lina Mulani; Maulana, Rizki; Mahir, Shafa; Fauzan, Wildan Tino; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
Weddings are the dream of many people, many wedding organizers are willing to provide luxury wedding facilities with lots of available equipment. The number of orders varies. Various numbers of orders received from customers who are made and received at the Wedding Organizer Administration for teenagers and adults, many are also among Weddings, the number of data searches requires a lot of time and effort by means of a manual system. Many people are starting to look for a place for this Wedding Organizer by visiting the place where the wedding is being held or directly visiting the Wedding Organizer to find information about the wedding building and wedding booking schedules. Sometimes this way of ordering Wedding Organizers makes people feel difficult, because they have to come first and then look for an empty booking schedule, it turns out that the Wedding Organizer's booking schedule is full. This will be very efficient and effective for services for tenants and owners of Wedding Organizers, because there is no internet-based information system. This study aims to create a web-based Wedding Organizer application, using PHP and MySQL to overcome existing problems, making it easier for tenants to get information about ordering Wedding Organizers for weddings. In addition, the owner of the Wedding Organizer can also manage the Wedding Organizer transaction data more accurately, so the author needs to design a Web-Based Wedding Organizer System Application to help the Wedding Organizer manager. This implementation resulted in the Web-Based Wedding Organizer System application, namely to facilitate ordering in the management of the Wedding Organizer report archiving which used to still use manual techniques so that now they use modern techniques or digital techniques, and this makes it easier for customers to make orders.